Novel coronavirus pneumonia during ophthalmic surgery management strategy and recommendations - Yong-Hui HUANG; Shan-Shan LI; Xi YAO; Ying-Rui YANG; De-Hua QIN; Jun-Mei ZHANG (Yixue xinzhi zazhi)
To summarize the experience of 4,761 patients who underwent ophthalmic surgery during the COVID-19 epidemic without iatrogenic and cross-infection, surgically related complications, and zero infection among medical staff. To explore environmental preparation for eye surgery during the COVID-19 epidemic, protective measures for medical staff and patients, isolation and transport of patients, medical waste disposal, interoperative terminal treatment.Recommendations for management strategies and infection prevention and control during COVID-19 epidemics, as well as preventive and control measures for ophthalmic surgery should be recommended.